A soft tactile sensor featuring subcutaneous tissue structure with collagen fibers. (4th March 2021) - Sonoi, Y.; Tanaka, Y.; Nishizawa, J.; Usuda, N.
Abstract : The human skin has amplifier functions for tactile sense. Pacinian corpuscles of mechanoreceptors are sensitive to vibrotactile stimulation, despite their distributions in the deep portion in the skin. Collagen fibers within the subcutaneous tissue help in the transmission of stress to the deep portion. The sensing elements embedded in the deep portion can soften the tactile sensors and provide robustness for the sensing function. Inspired by the configuration of collagen fibers in monkey fingertips, this study proposes a soft tactile sensor containing a fiber structure. The sensor consists of three layers: the epidermis, dermis, and subcutaneous tissue, represented by natural rubber, elastomer resin, and urethane resin, respectively. The fiber structure made of the elastomer resin is in the form of quadrangular pyramids, with pillars expanding from the dermis layer to the bottom layer inside the urethane resin. Strain gauges are embedded in the shallow and deep portions of the sensor. Finite element analysis and experiments on the spatial responses and basic characteristics of the frequency and force were conducted. The results showed that the tactile sensor with a fiber structure has a higher sensitivity to vibrotactile stimulation in the deep portion than the sensor with a uniform structure. GRAPHICAL ABSTRACT: UF0001